Odpowiedzi

2010-03-08T17:12:47+01:00
A) 4x+8-3y+3=x+y-3
B) 3x-12-2y+4=4x-4y+4

A) 4x-3y-x-y=-3-3-8
B) 3x-2y-4x+4y=4+12-4

A) 3x-4y=-14
B) -1x +2y=12 wyznaczam x z B x=2y-12 i wstawiam do A
3(2y-12) - 4y = -14
6y-36 - 4y = -14
2y=-14+36
2y=22 y=11
x=2*11-12=22-12=10

x=10 y=11
1 5 1
2010-03-08T17:15:25+01:00

4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x+8-3y+4=x+y-3
3x-12-2y+4=4x-4y+4

3x-4y=-16
-x+2y=12 /*2

-3x-4y=-16
-2x+4y=24

-5x=8 /:-5
x=-1,6

3*(-1,6)-4y=-16
11,2=4y /:4
y=2,8
x=-1,6
1 5 1
Najlepsza Odpowiedź!
2010-03-08T17:39:57+01:00
4(x+2)-3(y-1)= x+y-3
3(x-4)-2(y-2)= 4(x-y)+4

4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y+4

3x-4y=-14
-x+2y=12

3x-4y=-14
-2x+4y=24

x=10
-10+2y=12
2y=22
y=11

y=11
x=10